Kinerja Pegawai Ditinjau dari Kompetensi, Disiplin Kerja, dan Budaya Organisasi pada SMA Negeri Mojogedang - Anggun Firdaus Sayekti; Bambang Mursito; Ratna Damayanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this study is to determine the specific influence of competency, work discipline, and organisational culture on the performance of employees at Mojogedang State High School. This study applies a quantitative descriptive technique and employs a saturation or census sample. Data was collected using dispersed questionnaires. The data underwent analysis using the t test, multiple linear regression, and coefficient of determination (R2). The research findings suggest that both competency and organisational culture significantly and positively influence employee performance. Nevertheless, work discipline has a favourable albeit insignificant influence on employee performance.